Fabrication of a controlled-release delivery system for relieving sciatica nerve pain using an ultrasound-responsive microcapsule - Xu, Xiong; Chang, Shuai; Zhang, Xiaoyi; Hou, Taotao; Yao, Hui; Zhang, Shusheng; Zhu, Yuqi; Cui, Xu; Wang, Xing (Frontiers in Bioengineering and Biotechnology, 2022)
Lidocaine, as a potent local anesthetic, is clinically used in nerve block and pain management. However, due to its short half-life, repeated administration is required in clinical practice. For this reason, here we designed and prepared a lidocaine-encapsulated polylactic acid-glycolic acid (Lidocaine@PLGA) microcapsule with ultrasound responsiveness for relieving the sciatica nerve pain. In views of the premixed membrane emulsification strategy, the fabricated lidocaine-embedded microcapsules possessed uniform particle size, good stability, injectability and long-term sustained release both in vitro and in vivo. More importantly, Lidocaine@PLGA microcapsules had the function of ultrasonic responsive release, which made the drug release controllable with the effect of on-off administration. Our research showed that ultrasound as a trigger switch could promote the rapid release of lidocaine from the microcapsules, achieving the dual effects of long-term sustained release and short-term ultrasound-triggered rapid release, which will enable the ultrasound-responsive Lidocaine@PLGA microcapsules in application of nerve root block and postoperative pain relief.